Pengawasan Pergudangan Di Kota Makassar - Pangestu, Fitri Putri; Ansari, Muh Isa; Malik, Ihyani (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
The purpose of this study was to find out the Methods and Stages of Warehousing Supervision in Makassar City. The number of informants were 8 people. This study used a qualitative research with a case study type. Data collection techniques were interviews, observation and documentation studies. Data analysis refered to Miles Huberman data analysis. The results of this study showed warehouse supervision in the city were seen from two aspects, namely the method and stages of supervision. The method of supervision carried out by the Department of Trade had been carried out with several methods such as direct and indirect supervision. This supervision method involved the role of the Trade Office employees as well as the roles of people outside the Trade Office such as the sub-district head, village head, and the community. While the stages of supervision at Makassar City Trade Office related to warehousing in Makassar City were very structured, starting from receiving reports related to violations of the warehousing business area and then issuing the first warning letter and carrying out supervision to the issuance of the third warning letter.Keywords: Supervision, Warehousing